A coordinated frequency control strategy for photovoltaic system in microgrid. Issue 1 (1st January 2018) - Lyu, Xue; Xu, Zhao; Zhao, Jian
Abstract: This paper proposes a coordinated DC-link voltage control and deloading control for two-stage PV system to offer frequency support in an islanded microgrid without energy storage system(ESS). The energy stored in the DC-link capacitor is utilized to emulate inertia response, which has an important implication on enhancing system inertia, since PV systems are equipped with power-electronic converter and have no natural inertia response. At the same time, a certain of power margin is reserved by increasing dc voltage of PV array, which provides PV system the ability to participate in primary frequency control. Simulations are conducted in DIgSILENT/ PowerFactory and results show that the proposed strategy is effective in improving the dynamic behavior of system frequency.